Implementation of an Integrated Project Based Learning Model for Generic Science Skills in Acid-Base Material - Tisa Florensia Ginting; Ratu Evina Dibyantini (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This research aims to determine the effect of Evaluation of Prior Knowledge and Student Worksheets on Evaluation of Learning Outcomes and determine the difference in learning outcomes between high initial knowledge and low initial knowledge using the Project Based Learning model integrated with Generic Science Skills in Acid-Base material. This research has two independent variables, namely Initial Knowledge Evaluation and Learner Worksheet and one dependent variable, namely Evaluation of learning outcomes data. The population in this study were all class XI students of SMA Negeri 2 Kabanjahe consisting of 6 classes. The sample in this study was taken using a purposive sampling technique from 1 class, namely class. The instruments used are initial knowledge evaluation test instruments, learning outcome evaluation test instruments and Student Worksheets as well as non-test student observation sheets. Data were analyzed using multiple linear regression tests and Independent Sample T-Test. The results of data analysis show that there is a significant influence between the value of Prior Knowledge and Student Worksheets on learning outcomes and there is a significant difference in the value of learning outcomes between students whose initial abilities are classified as high and students whose initial abilities are classified as low.